Assessing and addressing literacy needs : cases and instructional strategies - Combs, Barbara (Los Angeles, Calif. : SAGE, 2012)
'Assessing and Addressing Literacy Needs: Cases and Instructional Strategies is designed to help preservice and inservice teachers understand the problems that children encounter when learning to read and to provide key instructional strategies related to best practices in literacy instruction. The text promotes reflection and analysis that will provoke thoughtful responses and discussions to help teachers use assessments to identify problems and employ appropriate strategies to help their students become better readers'-- Provided by publisher.
Machine generated contents note: About the AuthorAcknowledgmentsPrefaceChapter 1: Introduction to Literacy Assessment and InstructionChapter 2: Focus on Emergent LiteracyChatper 2: Focus on Word IdentificationChapter 3: Focus on FluencyChapter 4: Focus on VocabularyChapter 5: Focus on ComprehensionChapter 6: Focus on EngagementGlossaryIndex.
Includes bibliographical references and index.
Keywords: Reading -- Remedial teaching; Reading -- Ability testing; Reading teachers -- Training of